Shear bond strengths of saliva contaminated 'one-bottle' adhesives - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2002)
The aim of this study was to investigate the effect of saliva contamination on the bond strengths of three one-bottle bonding systems. The dentin of 90 recently extracted, non-carious human molar teeth was exposed and ground wet on 500 grit silicon carbide (SIC) paper to establish a bonding surface in superficial dentin. Specimens were randomly assigned to nine groups of 10 teeth each. Three testing conditions are: (i) contamination with fresh saliva (pH 5.5) after acid etching, (ii) contamination with fresh saliva after bonding application, and (iii) no contamination. Three adhesive systems are: syntac single component, prime & bond NT, and gluma one bond. Cylinders of composite were applied via PTFE (polytetrafluroethylene) split mould and light cured to the dentin surfaces. All specimens were thermocycled (5000 cycles) between baths of 5 and 55 degreesC. Shear bond strengths were measured using an Instron Universal testing machine at a crosshead speed of 1 mm min(-1) . Two-way ANOVA was used to analyse the data. The results of this study indicated that the saliva contamination of dentin has no adverse effect on the bonding efficiency of one-bottle adhesive systems (P > 0.05). No statistically significant differences were found between the shear bond strengths of tested adhesives.
Keywords: one-bottle adhesive system; saliva contamination; shear bond strength; DENTIN; AGENTS